Time perspective and family history of alcohol dependence moderate the effect of depression on alcohol dependence: A study in Chinese psychiatric clinics - Wang, Haiyan; Zhu, Yichen; Shi, Jie; Huang, Xiaoyu; Zhu, Xiaoying (Frontiers in Psychology, 2022)
Background: Depression and alcohol dependence (AD) are among the most prevalent psychiatric disorders and commonly co-occur. Gaining a better grasp on factors related to this comorbidity is of particular interest for clinicians. Past research has highlighted the significant role time perspective and family history of alcohol dependence (FH) plays in depression and AD. However, much remains at stake in the understanding of the association between them. The objective of this research is to explore how temporal profile and other sociodemographic characteristic in patients diagnosed with AD would impact their severity of depression and AD. Methods: This study was a multi-centered study, which included 381 patients and collected cross-sectional information in both inpatient and outpatient psychiatric clinics in China. Data was acquired using validated self-report scales, including MAST, SDS, and ZTPI-C. Multiple linear regression analyses were conducted to control social demographic variables and construct prediction models to inspect the influence factors of variables. Moderation models were constructed to further inspect interplay between variables using hierarchical regression and PROCESS Macro. Results: In our study, among all the patients who had been diagnosed with alcohol dependence according to ICD-10 in Chinese psychiatry clinics, 59.9% of them met the criteria of depression according to questionnaire. By using regression analysis, we found time perspective could predict severity of depression and AD. The moderating role of past negative and FH was confirmed between depression and AD. Only in patients with FH+ and moderate to high score of past negative compared to other participants, the severity of depression would predict the severity of alcoholism.